"SP-G", a Putative New Surfactant Protein - Tissue Localization and 3D Structure - Rausch, Felix; Schicht, Martin; Paulsen, Friedrich; Ngueya, Ivan; Bräuer, Lars; Brandt, Wolfgang (PLoS ONE, 2012)
Surfactant proteins (SP) are well known from human lung. These proteins assist the formation of a monolayer of surface-active phospholipids at the liquid-air interface of the alveolar lining, play a major role in lowering the surface tension of interfaces, and have functions in innate and adaptive immune defense. During recent years it became obvious that SPs are also part of other tissues and fluids such as tear fluid, gingiva, saliva, the nasolacrimal system, and kidney. Recently, a putative new surfactant protein (SFTA2 or SP-G) was identified, which has no sequence or structural identity to the already know surfactant proteins. In this work, computational chemistry and molecular-biological methods were combined to localize and characterize SP-G. With the help of a protein structure model, specific antibodies were obtained which allowed the detection of SP-G not only on mRNA but also on protein level. The localization of this protein in different human tissues, sequence based prediction tools for posttranslational modifications and molecular dynamic simulations reveal that SP-G has physicochemical properties similar to the already known surfactant proteins B and C. This includes also the possibility of interactions with lipid systems and with that, a potential surface-regulatory feature of SP-G. In conclusion, the results indicate SP-G as a new surfactant protein which represents an until now unknown surfactant protein class. © 2012 Rausch et al.
CRIS-Team Scopus Importer:2022-08-05